2020
DOI: 10.17765/2176-9168.2020v13n4p1447-1469
|View full text |Cite
|
Sign up to set email alerts
|

Carbono orgânico e estoque de carbono do solo em diferentes sistemas de manejo

Abstract: O presente estudo teve como objetivo avaliar os teores de carbono orgânico total (COT) e os estoques de carbono (EstC) em diferentes sistemas de manejo conduzidos ao longo do tempo no município de Iguatemi (MS), Brasil. Foi utilizado o delineamento inteiramente casualizado com quatro repetições, sendo estudadas quatro áreas situadas em uma mesma propriedade rural, conduzidas com diferentes sistemas de manejo, sendo elas: lavoura em sistema de preparo convencional, pastagem permanente e eucalipto, além da área … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
3
5
0
3
Order By: Relevance
“…17 n. 5, e2814 -Taubaté 2022 The areas of PP and PNHR, due to the arrangement of the groups, did not contribute effectively to the improvement of the edaphic quality within the parameters evaluated, and only the NTS area was closer to the NF. Rosset et al (2014;; Martins et al (2020) and Troian et al (2020) also observed the same behaviors found in this study, with the NF area of vegetation of the Atlantic Forest biome having better edaphic quality in relation to the other managed areas. Rosset et al (2019) observed similarities between the areas of PP and NF.…”
Section: Analysis Of Principal Components and Correlation Between Var...supporting
confidence: 86%
“…17 n. 5, e2814 -Taubaté 2022 The areas of PP and PNHR, due to the arrangement of the groups, did not contribute effectively to the improvement of the edaphic quality within the parameters evaluated, and only the NTS area was closer to the NF. Rosset et al (2014;; Martins et al (2020) and Troian et al (2020) also observed the same behaviors found in this study, with the NF area of vegetation of the Atlantic Forest biome having better edaphic quality in relation to the other managed areas. Rosset et al (2019) observed similarities between the areas of PP and NF.…”
Section: Analysis Of Principal Components and Correlation Between Var...supporting
confidence: 86%
“…2020. Troian et al (2020) observed SI values of 2.00, 1.85, and 1.08, respectively, in areas of permanent pasture in the state of Mato Grosso do Sul. Moreover, Rosset et al (2014) found a value of 1.78 in a pasture area managed for 38 years in the state of Paraná.…”
mentioning
confidence: 86%
“…The TOC contents of the different areas in the 0-0.05 m layer ranged from 7.28 g kg -1 to 16.42 g kg -1 , with higher content in the NF area (Figure 3). This higher content of TOC in the NF in the surface layer is due to the continuous deposition of plant material from litter (branches, leaves, flowers, fruits, and tree bark) on the soil surface , in addition to lower losses by erosive processes (Barros et al 2013), as well as the absence of anthropic activity in this location, as observed by Rosset et al (2014;2016;, Assunção et al (2019) and Ferreira et al (2020) comparing managed areas and native vegetation of Atlantic Forest in Guaíra, PR, by Ozório et al (2019; in Terra Roxa, PR and Martins et al (2020) and Troian et al (2020) in Iguatemi, MS.…”
Section: Resultsmentioning
confidence: 91%